Intraseasonal variability of rainfall over northern south america and caribbean region (2008)
Based on decadal (amounts for each ten days) precipitation data from meteorological stations situated in Northern South America and Caribbean region, a decadal precipitation index (DPI) was calculated in order to study the intraseasonal variability (ISV) of regional rainfall. The spectral analysis of DPI allows to identify signals with20-25, 30, 40 and 50-60 days period. According to the analysis of their spatial distribution these signals are well defined over the Caribbean island and coastal sector such as in some sectors of the Andean region; the 60-days signal is presented only over Caribbean region and in some places in the Pacific sector; in the eastern lowlandsof Orinoco and Amazon basin these signals are not clearly expressed.Exploring the relationship between regional ISV and Madden-Julian Oscillation correlation analysis was made.Due to the presence of signals different of 30-60 days, the correlation coefficients were very low. Considering this situation, high frequency smoothing was applied to DPI time series; after that, a relative correlation was detected between smoothed DPI and Madden-Julian Index (MJI).